Real-time monitoring using AJAX and WebSockets. Issue 1 (2nd January 2020) - Gupta, Yash; Dewan, Himanshu; Leekha, Alka
Abstract: The primary method for facilitating asynchronous communication over the Web is asynchronous JavaScript and XML (AJAX). Although AJAX provides the Web with warranted real-time functionality, unconventional techniques of programming are required at the cost of extensive use of resources. Implementing asynchronous communication over the Web, WebSockets, which is an emerging protocol, has the potential to address many challenges. There has been no independent study analyzing AJAX and WebSockets quantitatively. This paper, therefore, provides the following contributions to integrating Web technologies in realtime systems. First, it quantitatively compares AJAX and Websocket performance in terms of connection time by varying the number of requests over the web. Second, it compares the data bytes transferred by varying the number of requests. Third, it quantitatively compares network bandwidth consumption between AJAX and WebSocket